Electronic student feedback management system based on web development - Fahad Layth Malallah; Jamal Mahmood; Mahmood Alfathe; Mohammed A. M. Abdullah (Science in Information Technology Letters, 2020)
Nowadays, operation management performed by electronic systems in different life sectors is distributed and expanded swiftly due to several advantages that can be achieved, such as time reduction process, simplicity, and high accuracy of running operations. In the educational sector, performing student feedback electrolytically (using PC, Tablet, or Mobile) rather than the ordinary paper-based methods saves staff and students' time and makes managing the data easier. This paper proposes a new approach for the Electronic Student Feedback Management System based on web programming, which consists of input, process, store, and retrieves information using a database. The system is based on the Accreditation Board for Engineering and Technology (ABET) questionnaire model, which is implemented using web development tools (HTML, CSS, Javascript, MySQL, and PHP with Apache web-server). As a result, the proposed system was implemented successfully. The Electronic Engineering College officially adopted it at Ninevah University to perform the student feedback for the academic year 2018-2019, in which 4,282 student feedback applications (SFA) have been recorded. After that, statistical operations were done for extracting useful information effortlessly and accurately. As a result, more than 800 students made 4282 records have participated in the proposed system. This information can be quickly recorded and utilized to identify the weaknesses to address them in the next academic year.